Respuesta :

[tex]\displaystyle 2x^2 - 8x = - 7 \\ \\ 2x^2-8x+7=0 \\ \\ \Delta=b^2-4ac \\ \\ \Delta=(-8)^2-4\cdot2\cdot7 \\ \\ \Delta = 8 \\ \\ X_{1,2}= \frac{-b\pm \sqrt{\Delta} }{2a} = \frac{8 \pm 2 \sqrt{2} }{4} = \frac{\not2(4\pm \sqrt{2}) }{\not4} = \frac{4\pm \sqrt{2} }{2} [/tex]
Making one side of the equation zero, the equation becomes,
                                  2x² - 8x + 7 = 0
The value of x may be calculated through the quadratic formula.
                                  x = (-b +/- sqrt(b² - 4ac)) / 2a
where a, b, and c are 2, -8, and 7, respectively. The values are,
                  x = (8 + sqrt (8² - (4)(2)(7))) / 2x2 = -1.29
                  x = (8 - sqrt (8² - (4)(2)(7))) / 2x2 = -2.71